PENGARUH DISIPLIN KERJA, GAYA KEPEMIMPINAN DAN KEPUASAN KERJA TERHADAP KINERJA GURU DI SMA NEGERI 7 PALU - Oslan, Oslan (Katalogis, 2015)
This research intends to explore and analyze simultaneous and partial influence of work discipline,leadership style, and work satisfaction on teachers’ performance in SMAN 7 Palu. Sample of this study consists of 42 teachers and its data analysis technique is multiple linear regressions. The results show that work discipline, leadership style, and work satisfaction simultaneously have significant influence on teachers’performance in SMAN 7 Palu. Partially,Work discipline has significant influence on teachers’ performance in SMAN 7 Palu: Leadership style has significant influence on teachers’ performance in SMAN 7 Palu; Work satisfaction has significant influence on teaches’ performance in SMAN 7 Palu. The value of adjusted R –squer of 0,611 indicates that 61,10 % of teachers’ performance in SMAN 7 Palu is affected by work discipline, leadership style, and work satisfaction. While 38.90% affected by other variables that are not studied.